Seeing COVID-19 through a Health care professional’s eye - Eesha Yaqoob, Saad Javed, Adeela Rehman, Mudassar Fayaz, Maryam Salma Babar, Ayesha Nasir, Eesha Yaqoob, Saad Javed, Adeela Rehman, Mudassar Fayaz, Maryam Salma Babar, Ayesha Nasir (Journal of Rawalpindi Medical College, 2022)
Background: The world is in a state of war. The health care professionals are the front line soldiers who are fighting this war against COVID-19. The modification in human behavior to a specific stimulus (say the Corona epidemic) is the single most important determinant of the fate of that stimulus. On 26th February 2020, Pakistan reported its first corona positive cases. Till Mid-March, the number raised to a significantly critical level. As the outbreak was unexpected in Pakistan, the situation created chaos and panic among the public as well as among health care workers. The current study analyzed COVID-19 thorough a healthcare professional’s eye. There has been no previous study according to the PubMed database. Using the keywords, "Coronavirus, Health care professionals, Pakistan, COVID-19", for any sort of previous cases reported or literature reported relating to coronavirus, our team could not find any article, case report or publication of any sort. So this study is the first from Pakistan Methods: In this cross-sectional study, a self-administrated online questionnaire was circulated through emails and social media to the whole country. The questionnaire comprised of assessing knowledge about the cause and symptoms of COVID-19. A total of 146 responses were scrutinized to include in the survey, in the time period of 1 week (March 23-30, 2020). The participants belonged to private and government institutions from all provinces of Pakistan. Results: The mean values of all items depicted that all health care professionals were well aware of the knowledge, symptoms and transmissibility of COVID-19. Conclusion: The study concluded that the healthcare professionals were fully aware of the transmission of COVID-19 and its symptoms. However, it is recommended that the government should provide full support to health care professionals, who are at the front line.